Juxtaposition of Barrovian and migmatite domains in the Chinese Altai: a result of crustal thickening followed by doming of partially molten lower crust. (11th November 2014) - Jiang, Y. D.; Štípská, P.; Sun, M.; Schulmann, K.; Zhang, J.; Wu, Q. H.; Long, X. P.; Yuan, C.; Racek, M.; Zhao, G. C.; Xiao, W. J.
Abstract Ordovician metasedimentary rocks are the oldest and most extensive sedimentary sequence in the Chinese Altai. They experienced two major episodes of deformation (D1 and D2) resulting in the formation of juxtaposed Barrovian‐type and migmatite domains. D1 is characterized by a penetrative sub‐horizontal fabric (S1), and D2 is marked by upright folds (F2) with NW–SE‐trending axial planes in shallow crustal levels and by sub‐vertical transposition foliations (S2) in the high‐grade cores of large‐scale F2 antiforms. In the Barrovian‐type domain, successive growth of biotite, garnet and staurolite is observed in the S1 fabric. Kyanite included in garnet and plagioclase in the migmatite domain is interpreted to have formed also in S1. In the biotite and garnet zones, the spaced S2 cleavage is marked by biotite and muscovite, and in the staurolite and kyanite zones, the penetrative S2 fabric is characterized by sillimanite, locally with late cordierite. Phase equilibria modelling indicates that the S1 fabric was associated with an increase in pressure and temperature under Barrovian‐type conditions in both domains. The S2 fabric was related to decompression, in which rocks in the biotite and garnet zones well preserve the peak assemblage, and the higher grade rocks in the staurolite and kyanite zones re‐equilibrated to different degrees under high‐temperature/low‐pressure (HT/LP) conditions. The D1 metamorphic history is attributed to the progressive burial related to Early–Middle Palaeozoic crustal thickening and the metamorphism associated with D2 is interpreted to result from exhumation by vertical extrusion. The extrusion of hot rocks was contemporaneous with the formation of gneiss domes accompanied by the intrusion of juvenile magmas at middle crustal levels during the Middle Palaeozoic. Consequently, there is a genetic link between the Barrovian‐type and migmatite domains related to continuous transition of the Barrovian‐type fabric into the HT/LP one during development of domal structures in the southern Altai orogenic belt. This study has a broad impact on the understanding of the thermo‐mechanical behaviour of accretionary orogenic systems worldwide. The lower crustal flow and doming of hot crust, so far reported only in continental collisional settings, seems to be also an integral mechanism responsible for both horizontal and vertical redistribution of accreted material prior to continental collision.